KNOWLEDGE TRANSLATION: INTEGRATING AGING RESEARCH AND INNOVATION INTO POLICY AND PRACTICE - Battersby, L. (Innov Aging, 2017)
Knowledge translation (KT) is an iterative process for bridging research, policy and practice that can be integrated into research and development to support the relevance and application of research findings. KT includes the mobilization of experiential and scientific knowledge through to the commercialization and application of research innovations. Building KT into research projects is nascent in gerontology, yet articulation of a KT strategy for research impact beyond traditional end-of-grant dissemination is a funding requirement. Integrating KT effectively into research is a complex process that is often misapplied. This symposium will present four cross-disciplinary, Canadian projects that demonstrate critical elements for effective KT in aging research. Grigorovich et al. detail mechanisms of transdisciplinary working, essential for integrated KT, alongside the development and validation of an effectiveness scale used to support transdisciplinary working in research. Demonstrating the first step of any KT initiative, Canham et al. present methods and findings from an applied realist review that explored the current state of the digital divide for older adults. At the other end of the KT process, Fang et al. report on an evaluation of the impact of a knowledge mobilization initiative for aging and technology innovation. Finally, Battersby et al. present findings from an integrated KT project that collaboratively developed, validated, and disseminated national guidelines for conducting mass interinstitutional relocations in long-term care. The symposium will conclude with a discussion led by a KT expert on the implications of using KT to bridge aging research and innovation with policy and practice.